PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA ASUHAN KEPERAWATAN DI RS LABUANG BAJI - Andi Niartiningsih; Muhammad Takwa; Nurul Hidayah Nur; Nurfitriani; Mene Paradilla (Advantage: Journal of Management and Business, 2024)
Performance is the work result that can be achieved by a person or group of people in an organization, in accordance with their respective authority and responsibilities in order to achieve the goals of the organization concerned legally, without violating the law and in accordance with morals and ethics. So it can be said that performance is important for a company or organization. The aim of the research is to analyze the influence of job satisfaction and transformational leadership on the performance of nursing care in the Inpatient Installation of Labuang Baji Hospital, Makassar. This type of research is quantitative research using a cross sectional study design, with a total sample of 103 nurse respondents. The sampling technique used in this quantitative research is Total Sampling. The research results showed that transformational leadership had an effect on nursing care performance (0.000<0.05). For hospital management, in order to improve employee performance, transformational leadership should be prioritized by the head of the room because based on research results, the transformational leadership variable has a big influence on employee performance. Leaders should always encourage employees to work in accordance with the vision, mission and goals of the organization, then motivate employees to work in accordance with work procedures and direct employees to comply with work mechanisms.